Relevant topics in the interpretation of chemometric data - Pereira-Filho, Edenir; Pereira, Fabiola [UNESP] (Elsevier, 2024)
This chapter shows several aspects of initial data inspection, focusing on outlier detection, hypothesis tests, and descriptive statistics. Data treatment and preprocessing are also the subject of this chapter, and the main differences were presented. In the end, some aspects related to principal component analysis and exploratory analysis were also discussed.
Keywords: analytical chemistry analysis; chemometrics; exploratory analysis; Outlier detection; principal component analysis; spectroanalytical; statistics; statistics for research